On the maturity and spawning of an ornamental fish, Erethistes pussilus Muller & Troschel - Phukon, J; Biswas, S P (Indian Journal of Fisheries, 2011)
Certain aspects of the reproductive biology of an ornamental fish,Erethistes pussilus have been studied from the Brahmaputra drainagesystem in Upper Assam. The length at first maturity of the species iscalculated at 5.2 cm for male and 6.7 cm for female. Ova diameter study,gonadosomatic ratio and histological studies of gonadal developmentindicate that the fish matures in May-June. It has a short breeding season(July-August). The absolute fecundity ranged from 1,312 to 3,744whereas, the relative fecundity varied between 220 and 1672. The speciesis an isochronal spawner with moderate fecundity